Penanaman Sikap Nasionalisme Religius Melalui Kegiatan Ekstrakurikuler Hizbul Wathan(Studi Kasus Di Smp Muhammadiyah 7 Surakarta Tahun Pelajaran 2015/2016) - TRIYANTO, AGUS; , Dr. Ahmad Muhibbin, M.Si (2016)
This study aimed to describe the forms of religious nationalism planting through extracurricular activities Hizbul Wathan in SMP Muhammadiyah 7 Surakarta in the academic year 2015/2016, the various obstacles faced and the solutions provided. The study used a qualitative approach, data collection is done with documentation, observation and interviews. Test the validity of the data with the triangulation of sources and techniques. The data analysis applying interactive models through data collection, data reduction, presentation and conclusion. The results showed that to inculcate religious nationalism in the students who participated in extracurricular Hizbul Wathan can be done in a way to familiarize students to participate in the flag ceremony, wearing Indonesian is good and right, buy the products in the country, praying on time, being honest , fair, patient with others known to inculcate in students' religious nationalism. Barriers experienced that first came from teachers or coaches, lies in the lack of builder Hizbul Wathan, causing the process of planting less than the maximum, besides the obstacles also come from the majority of students are still indifferent, unruly, and less able to work together the success of the programs implemented school as planting efforts in the nominally religious nationalism. Solutions provided the school is always working to increase the number of coaches Hizbul Wathan and familiarize students to be religious nationalism in everyday life by providing knowledge to students about the importance of having the attitude of religious nationalism, invites students to pray on time, etc.